Macrozoobentos Community Structure at Ecoshrimp Reservoir Pond, Waetuoe Village, Lanrisang District, Pinrang Regency - Nasir, Nur Asra; Tresnati, Joeharnani; Fajriyati Inaku, Dwi; Nadiarti; Irmawati (Hasanuddin University, 2024)
Mollusc has great commercial benefits in capture fisheries and aquaculture. However, it can also cause economic losses and human suffering. Some macrozoobenthos of the mollusc species are intermediate hosts for parasites and pests in aquaculture pond systems. The reservoir in the pond is a sedimentation area and a biofilter to optimize water quality before flowing into the pond. This study aims to analyze macrozoobenthos community structure at the ecoshrimp reservoir pond located in Waetuoe Village, Lanrisang District, Pinrang. Macrozoobenthos sampling was carried out using a 1x1 m quadrant-transect. The results showed that the identified molluscs consisted of eight species grouped into four families and two classes, including Gastropods and Bivalves. The abundance of macrozoobenthos at the pond's edge was smaller than those in the middle part (994 individuals vs. 1095 individuals). Sermyla requtii was the species with the highest density of 350 ind/m2 at the edge and 670 ind/m2 in the middle of the reservoir. The frequency of occurrence of macrozoobenthos at both observation sites has a value of > 25%. The diversity index at the edge of the reservoir (1.7015) and in the middle of the reservoir (1.2533) is relatively moderate. The uniformity index value at the edge of the reservoir (1.8620) and in the middle of the reservoir (1.3715) is relatively high. The dominance index value at the edge of the reservoir (0.2192) and in the middle of the reservoir (0.4124) is relatively low. The particle size analysis shows that the sediment type in the reservoir is medium sand with an average median value (d50) of 0.29 mm.